White City: A History of Place - Maddock, Gabriel (Curtin University, 2024)
Perth’s first modern amusement park, White City, opened in 1921. It was a divisive venue: favoured by its working-class patrons who returned year after year, detested by middle-class social reformers and church leaders who believed it was corrupting the people of Perth. Gabriel Maddock’s thesis investigates the history and significance of this notable Western Australian leisure site. The outcome of her research is two interconnected texts: a theoretical exegesis and a work of literary non-fiction.